Against procreative moral rights - Earl, Jake (Bioethics, 2022)
Many contemporary ethical debates turn on claims about the nature and extent of our alleged procreative moral rights: moral rights to procreate or not to procreate as we choose. In this article, I argue that there are no procreative moral rights, in that generally we do not have a distinctive moral right to procreate or not to procreate as we choose. However, interference with our procreative choices usually violates our nonprocreative moral rights, such as our moral rights to bodily autonomy or to privacy. My argument presents hypothetical cases in which a state interferes with a person's procreative choices in order to promote aggregate social welfare, but this interference does not violate any of the person's nonprocreative moral rights. These cases not only undermine frequently made claims that widely recognized nonprocreative moral rights entail procreative moral rights, they also challenge the intuitively plausible claim that interference with our procreative choices as such violates our moral rights. What at first appear to be substantive moral rights are in fact a kind of illusion created by the frequent overlap of other rights, but lacking in substance beyond that overlap. While this argument against the existence of procreative moral rights has substantive implications for ongoing debates in reproductive ethics, I ultimately suggest that it is consistent with a progressive approach to reproductive justice.